Pengaruh Program Pesantren, Sumber Daya Manusia, dan Lingkungan Pesantren Terhadap Kemandirian Santri Pondok Pesantren - Mujib, Ali; Egar, Ngasbun; Wuryandini, Endang (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The problems in this study are: (1) How much influence does the Islamic boarding school program have on the independence of students of Al Hidayah Islamic Boarding School, Plumbon? (2) How much influence does the Islamic boarding school Human Resources have on the independence of students of Al Hidayah Islamic Boarding School, Plumbon? (3) How much influence does the Islamic boarding school environment have on the independence of students of Al Hidayah Islamic Boarding School, Plumbon?;(4) Human Resources and the Islamic boarding school environment together have on the independence of students of Al Hidayah Islamic Boarding School, Plumbon? The purpose of this study was to determine: (1) The magnitude of the influence of the Islamic boarding school program on the independence of students at the Al Hidayah Plumbon Islamic Boarding School; (2) The magnitude of the influence of the Islamic boarding school's Human Resources on the independence of students at the Al Hidayah Plumbon Islamic Boarding School District (3) The magnitude of the influence of the Islamic boarding school environment on the independence of students at the Al Hidayah Plumbon Islamic Boarding School (4) The magnitude of the influence of the Islamic boarding school program, Human Resources and the Islamic boarding school environment together on the independence of students at the Al Hidayah Plumbon Islamic Boarding School.. The population of this study was all students at the Al Hidayah Plumbon Islamic Boarding School, totaling 1,186 people and the sample selected was 256 respondents. Data collection techniques were by questionnaire and documentation. The data analysis techniques used in this study are data description analysis, requirement testing and hypothesis testing which include simple regression analysis and multiple regression. Data analysis is SPSS for windows version 26. The results of the study are as follows: (1) There is a significant influence of the pesantren program on the independence of students with F_count values > F_table, namely 115.041 > 2.64 with a contribution of 31.2%; (2) There is a significant influence of human resources on the independence of students with F_count values > F_table, namely 183.109 > 2.64 with a contribution of 41.9%; (3) There is a significant influence of the pesantren environment on the independence of students with F_count values > F_table, namely 48.179 > 2.64 with a contribution of 15.6%; (4) There is a significant influence of the Islamic boarding school program, human resources and the Islamic boarding school environment on the independence of students with F_count > F_table, namely 75.215 > 2.64 with a contribution of 52.8%